Rhetoric and the law, or the law of rhetoric: How countries oppose novel tobacco control measures at the World Trade Organization. (September 2016) - Lencucha, Raphael; Drope, Jeffrey; Labonte, Ronald
Abstract: The tobacco industry has developed an extensive array of strategies and arguments to prevent or weaken government regulation. These strategies and arguments are well documented at the domestic level. However, there remains a need to examine how these arguments are reflected in the challenges waged by governments within the World Trade Organization (WTO). Decisions made at the WTO have the potential to shape how countries govern. Our analysis was conducted on two novel tobacco control measures: tobacco additives bans (Canada, United States and Brazil) and plain, standardized packaging of tobacco products (Australia, New Zealand, Ireland, EU and UK). We analyzed WTO documents (i.e. meeting minutes and submissions) (n = 62) in order to identify patterns of argumentation and compare these patterns with well-documented industry arguments. The pattern of these arguments reveal that despite the unique institutional structure of the WTO, country representatives opposing novel tobacco control measures use the same non-technical arguments as those that the tobacco industry continues to use to oppose these measures at the domestic level. Highlights: The World Trade Organization (WTO) has become a common forum for countries to oppose novel tobacco control measures. Little is known about the arguments used by country representatives at the WTO to oppose novel tobacco control measures. We analyze this opposition in order to identify the salient rhetorical frames. Rhetorical patterns of opposition at the WTO align closely with tobacco industry arguments at the national level.